2005
DOI: 10.1094/phyto-95-1438
|View full text |Cite
|
Sign up to set email alerts
|

Development of Crown and Root Rot Disease of Tomato Under Irrigation with Saline Water

Abstract: We studied the effect of water salinity on the incidence and severity of crown and root rot disease of tomato, as well as on the pathogen and on the plant's response to the pathogen. Irrigation with saline water significantly increased disease severity in tomato transplants inoculated with Fusarium oxysporum f. sp. radicis-lycopersici, and mineral fertilization further increased it. In one field experiment, disease incidence in plots irrigated with saline water (electrical conductivity [EC] = 3.2 +/- 0.1 dS m(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 33 publications
0
46
0
3
Order By: Relevance
“…Increased soil salt concentration results in enhanced susceptibility to soil borne diseases in tomato (Triky-Dotan et al 2005) and other crop species (Al-Sadi et al 2010;You et al 2011), and similar trends are observed under water deficit (Jordan et al 1984). Observations of the effects of abiotic stress on foliar pathogens are on the other hand mixed, with studies reporting either enhanced (Achuo et al 2006;Wiese et al 2004), or decreased resistance (Roubtsova and Bostock 2009;Sanogo 2004).…”
Section: Introductionmentioning
confidence: 67%
“…Increased soil salt concentration results in enhanced susceptibility to soil borne diseases in tomato (Triky-Dotan et al 2005) and other crop species (Al-Sadi et al 2010;You et al 2011), and similar trends are observed under water deficit (Jordan et al 1984). Observations of the effects of abiotic stress on foliar pathogens are on the other hand mixed, with studies reporting either enhanced (Achuo et al 2006;Wiese et al 2004), or decreased resistance (Roubtsova and Bostock 2009;Sanogo 2004).…”
Section: Introductionmentioning
confidence: 67%
“…Lateral spread of Forl within field rows has been observed and may occur through root contact and movement in irrigation water (McGovern and Datnoff, 1992). Symptoms of FCRR are enhanced by cool temperatures (10e20 C), water-logged soil, irrigation with saline water (Triky-Dotan et al, 2005) and, as with FW, by low soil pH and ammoniacal nitrogen.…”
Section: Symptomsmentioning
confidence: 99%
“…Crops tolerant to salt, like cotton and barley, can withstand EC levels above 7 dS m Ϫ1 ; most soils have an EC ranging from 2 to 4 dS m Ϫ1 , and seawater has an EC of 54 dS m Ϫ1 . High salinity may increase the severity of diseases caused by a variety of plant pathogens (15,43), and the search for new Trichoderma strains capable of overcoming extreme environmental conditions is timely.…”
mentioning
confidence: 99%